The Transferrin Receptor-Directed CAR for the Therapy of Hematologic Malignancies - Guo, Zilong; Zhang, Yirui; Fu, Mingpeng; Zhao, Liang; Wang, Zhen; Xu, Zhuoshuo; Zhu, Huifen; Lan, Xiaoli; Shen, Guanxin; He, Yong; Lei, Ping (Frontiers in Immunology, 2021)
As many patients ultimately relapse after chimeric antigen receptor (CAR) T-cell therapy, identification of alternative targets is currently being evaluated. Substantial research efforts are underway to develop new targets. The transferrin receptor (TfR) is prevalently expressed on rapidly proliferating tumor cells and holds the potential to be the alternative target. In order to investigate the efficacy and challenges of TfR-targeting on the CAR-based therapy strategy, we generated a TfR-specific CAR and established the TfR-CAR modified T cells. To take the advantage of TfR being widely shared by multiple tumors, TfR-CAR T cells were assessed against several TfR+ hematological malignant cell lines. Data showed that TfR-CAR T cells were powerfully potent in killing all these types of cells in vitro and in killing T-ALL cells in vivo. These findings suggest TfR could be a universal target to broaden and improve the therapeutic efficacy of CAR T cells and warrant further efforts to use these cells as an alternative CAR T cell product for the therapy of hematological malignancies.